Clonal Candidemia Outbreak by Candida parapsilosis Carrying Y132F in Turkey: Evolution of a Persisting Challenge - Arastehfar, Amir; Hilmioğlu-Polat, Suleyha; Daneshnia, Farnaz; Pan, Weihua; Hafez, Ahmed; Fang, Wenjie; Liao, Wanqing; Şahbudak-Bal, Zümrüt; Metin, Dilek Yeşim; Júnior, João N. de Almeida; Ilkit, Macit; Perlin, David S.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
As the second leading etiological agent of candidemia in Turkey and the cause of severe fluconazole-non-susceptible (FNS) clonal outbreaks, Candida parapsilosis emerged as a major health threat at Ege University Hospital (EUH). Evaluation of microbiological and pertinent clinical profiles of candidemia patients due to C. parapsilosis in EUH in 2019–2020. Candida parapsilosis isolates were collected from blood samples and identified by sequencing internal transcribed spacer ribosomal DNA. Antifungal susceptibility testing was performed in accordance with CLSI M60 protocol and ERG11 and HS1/HS2-FKS1 were sequenced to explore the fluconazole and echinocandin resistance, respectively. Isolates were typed using a multilocus microsatellite typing assay. Relevant clinical data were obtained for patients recruited in the current study. FNS C. parapsilosis isolates were recovered from 53% of the patients admitted to EUH in 2019–2020. Y132F was the most frequent mutation in Erg11. All patients infected with C. parapsilosis isolates carrying Y132F, who received fluconazole showed therapeutic failure and significantly had a higher mortality than those infected with other FNS and susceptible isolates (50% vs. 16.1%). All isolates carrying Y132F grouped into one major cluster and mainly recovered from patients admitted to chest diseases and pediatric surgery wards. The unprecedented increase in the number of Y132F C. parapsilosis, which corresponded with increased rates of fluconazole therapeutic failure and mortality, is worrisome and highlights the urgency for strict infection control strategies, antifungal stewardship, and environmental screening in EUH.